2022
DOI: 10.1128/spectrum.02537-22
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Long COVID and Its Association with the Presence of SARS-CoV-2 Antibodies in a Danish Cohort up to 12 Months after Infection

Abstract: This cohort study included questionnaire data as well as anti-nucleocapsid antibody analysis, allowing us to determine whether participants were seropositive due to vaccination or natural infection. The study emphasizes the importance of early confirmation of COVID-19, as antibodies recede with time, and it indicates an overlap between long COVID symptoms and symptoms possibly of another origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
3
0
2
Order By: Relevance
“…However, they also emphasize that the existing scientific evidence is limited and disposed to bias. A significant difference regarding sex and risk of experiencing prolonged COVID-19-related symptoms was observed, as females reported these symptoms at a higher frequency than males, in-line with previous studies [35]. Age appeared to have an impact on symptom presentation as well.…”
Section: Discussionsupporting
confidence: 87%
“…However, they also emphasize that the existing scientific evidence is limited and disposed to bias. A significant difference regarding sex and risk of experiencing prolonged COVID-19-related symptoms was observed, as females reported these symptoms at a higher frequency than males, in-line with previous studies [35]. Age appeared to have an impact on symptom presentation as well.…”
Section: Discussionsupporting
confidence: 87%
“…According to our results, showing significantly higher mean SARS-CoV-2 IgG titers in LC patients, immunological dysfunctions have been detected in different studies including long-COVID subjects. These studies have shown that LC patients had highly activated innate immune cells, elevated expression of type I IFN and type III IFN, with higher production of a pro-inflammatory cytokine such as IL-6, indicating that components of the acute inflammatory response are associated with long-COVID [ 42 , 43 , 44 ]. It is possible to infer that systemic inflammation is bidirectionally linked to oxidative damage in long-COVID; persistent inflammation generates ROS and lipid peroxidation, and redox imbalance causes cellular damage that evokes an inflammatory response, leading to a vicious cycle [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studying the long-term effects of COVID-19 (long COVID) among members of a Facebook group dedicated to individuals who suspect they may have sequelae from COVID-19 is innovative ( 1 ).…”
Section: Lettermentioning
confidence: 99%